THE EFFECT OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT PLN PERSERO ULTG JENEPONTO - Sufardin Idris (Scientium Management Review, 2022)
The purpose of this exploration is to determine the effect of leadership style and organizational culture on hand performance at PT PLN ULTG Jeneponto. Hand performance can be said to be the result of work in quality and volume achieved by an hand in carrying out his duties in agreement with the liabilities given to him. This study tries to dissect the effects that affect performance. The several factors assessed are leadership style and organizational culture. The location of this research focusing at PT PLN ULTG Jeneponto Office. The population of this study were all 113 workers of PT PLN ULTG Jeneponto, while the samples in this study were 113 people. The logical system used is path analysis. The results of this study concluded that leadership style has no effect on performance but organizational culture has a positive and significant effect on performance. The better the organizational culture that's applied in company, the more it encourages hand performance.